Does the form of delivering incentives in conditional cash transfers matter over a decade later? (2018)
We study whether Honduran children exposed to a conditional cash transfer program from 2000-2005 experiencelasting effects on human capital and labor market outcomes in early adulthood. The government randomlyassigned three forms of delivering program benefits across targeted municipalities: demand (vouchers), supply(clinic and school subsidies), and a combination of both. This program provides an opportunity to explore ifand how differential exposure to incentives produces longer term effects. Using municipal-level panel data, theseeffects are estimated using difference-in-differences. We find that the form of delivering cash transfers influencesthe degree to which these programs make progress towards their objective of reducing future poverty. Comparedto municipalities receiving support from the Honduran Poverty Reduction Strategy, our study indicates thatexposure to demand-side incentives individually has no lasting impact. However, joint exposure to both demand-and supply-side incentives does lead to measurable improvements in schooling and labor market participation.